SN 2014J at M82 – I. A middle-class Type Ia supernova by all spectroscopic metrics. Issue 1 (20th January 2016) - Galbany, L.; Moreno-Raya, M. E.; Ruiz-Lapuente, P.; González Hernández, J. I.; Méndez, J.; Vallely, P.; Baron, E.; Domínguez, I.; Hamuy, M.; López-Sánchez, A. R.; Mollá, M.; Catalán, S.; et al.
Abstract: We present the intensive spectroscopic follow up of the Type Ia supernova (SN Ia) 2014J in the starburst galaxy M82. Twenty-seven optical spectra have been acquired from 2014 January 22 to September 1 with the Isaac Newton and William Herschel Telescopes. After correcting the observations for the recession velocity of M82 and for Milky Way and host galaxy extinction, we measured expansion velocities from spectral line blueshifts and pseudo-equivalent width of the strongest features in the spectra, which gives an idea on how elements are distributed within the ejecta. We position SN 2014J in the Benetti, Branch et al. and Wang et al. diagrams. These diagrams are based on properties of the Si ii features and provide dynamical and chemical information about the SN ejecta. The nearby SN 2011fe, which showed little evidence for reddening in its host galaxy, is shown as a reference for comparisons. SN 2014J is a border-line object between the Core-normal and Broad-line groups, which corresponds to an intermediate position between low-velocity gradient and high-velocity gradient objects. SN 2014J follows the $R({\rm Si\, {\small {II}}})$ –Δ m 15 correlation, which confirms its classification as a relatively normal SN Ia. Our description of the SN Ia in terms of the evolution of the pseudo-equivalent width of various ions as well as the position in the various diagrams put this specific SN Ia into the overall sample of SN Ia.